2023
DOI: 10.1021/acs.jpca.3c00478
|View full text |Cite
|
Sign up to set email alerts
|

Carbonyl-Based Redox-Active Compounds as Organic Electrodes for Batteries: Escape from Middle–High Redox Potentials and Further Improvement?

Abstract: Extractingfrom the vast space of organic compoundsthe best electrode candidates for achieving energy material breakthrough requires the identification of the microscopic causes and origins of various macroscopic features, including notably electrochemical and conduction properties. As a first guess of their capabilities, molecular DFT calculations and quantum theory of atoms in molecules (QTAIM)-derived indicators were applied to explore the family of pyrano[3,2-b]pyran-2,6-dione (PPD, i.e., A0) compounds, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Lambert et al. have predicted the capabilities of a series of carbonyl-based redox-active compounds by DFT calculations, including the family of pyrano[3,2- b ]pyran-2,6-dione (PPD) derivatives fused with various kinds of rings (benzene, fluorinated benzene, thiophene, and merged thiophene/benzene) . It was found that the PPD compounds are suitable as the anode materials due to the low calculated redox potentials.…”
Section: Redox-active Feature For Electrodementioning
confidence: 99%
See 3 more Smart Citations
“…Lambert et al. have predicted the capabilities of a series of carbonyl-based redox-active compounds by DFT calculations, including the family of pyrano[3,2- b ]pyran-2,6-dione (PPD) derivatives fused with various kinds of rings (benzene, fluorinated benzene, thiophene, and merged thiophene/benzene) . It was found that the PPD compounds are suitable as the anode materials due to the low calculated redox potentials.…”
Section: Redox-active Feature For Electrodementioning
confidence: 99%
“…The DFT-based computational redox potentials are in good agreement with the experimental results within an uncertainty of ∼0.3 V, which implies the reliability of DFT method. The redox potential is decreased with the increase of aromaticity. , In addition, the redox potential can be increased by attaching electron-withdrawing functional groups. Bachman et.…”
Section: Redox-active Feature For Electrodementioning
confidence: 99%
See 2 more Smart Citations